Stratigraphy and Paleoenvironment of the Kuaro Formation, Muru River, Kutai Basin: A Paleontological Approach - Iwan Prabowo; Fathony Akbar Pratikno; Efrina Chandra Agusti Putri; Jamaluddin Jamaluddin; Eliza Putri Andrean; Imanuel Kaunang (JURNAL GEOCELEBES, 2026)
The southern margin of the Kutai Basin remains poorly constrained regarding its Paleogene history compared to the well-studied northern depocenter. This research investigates the stratigraphic characteristics, relative ages, and depositional environments of the Kuaro Formation along the Muru River, Paser Regency. The study integrates a detailed measuring section with biostratigraphic analyses of Larger Benthic Foraminifera (LBF), calcareous nannofossils, and palynology to reconstruct the paleoenvironmental evolution. The results reveal a continuous stratigraphic succession spanning from the Late Eocene to the Late Oligocene. The lower interval comprises coal-bearing siliciclastics deposited in a coastal swamp environment, marking the initial terrestrial influence. This unit transitions upward into massive Pellatispira and Discocyclina-bearing rudstones, indicating the development of a stable shallow-marine carbonate platform during the Late Eocene. The sequence culminates in Late Oligocene fine-grained calcareous claystones yielding Reticulofenestra bisecta and Reticulofenestra lockeri, deposited in a lower-energy inner shelf setting. This vertical stacking pattern records a major transgressive phase, evolving from terrestrial-influenced environments to open marine conditions. These findings provide significant insights into the Eocene–Oligocene transition in the southern Kutai Basin, distinguishing its retrogradational stratigraphic architecture from the progradational deltaic cycles typical of the younger Neogene sequences in the northern basin.